Utilização de lodo de estação de tratamento de água para produção de geopolímeros - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Geopolymers are cementitious materials obtained by the alkaline activation of amorphous solid precursor rich in silica and alumina. In this study the physical and mechanical properties of the geopolymers obtained from calcined Water Treatment Station Sludge (WTSS) are evaluated. The influence of the SiO2/Al2O3 molar ratio on the properties of the geopolymers was analyzed in which the sodium silicate obtained by the dissolution of active silica in 10 mol.L-1 sodium hydroxide solution was used as alkaline activator. The WTSS was collected in Manaus, benefiting mechanically and thermally in order to reduce particle size and organic load, respectively. It was found that calcination at 750 ° C for one hour was efficient to change the crystal structure of kaolin present in the WTSS. The geopolymers obtained from calcined WTSS presented low values of specific mass and time of handle, high values for porosity, water absorption and resistance to compression. In this work the potential of the use of calcined WTSS for the production of geopolymers was analyzed, whose result suggests the compatibility in the development of this material.
Keywords: Geopolímero; Lodo de estação de tratamento de água; Resíduos industriais; Ativação alcalina; Geopolymer; Sludge from water treatment plant; Alkaline activation; ENGENHARIAS: ENGENHARIA CIVIL